Samelisant, an H3 Receptor Agonist as an Anti-Alzheimer Potential – A Pilot Study on Molecular Docking - Sumathi Thangarajan; Annie Aishwarya Sundar (International Journal of Brain Sciences, 2026)
Neurodegenerative diseases have become more prevalent and about 55 million of the population are affected by dementia globally. One of the most important neurodegenerative diseases is Alzheimer’s disease which is known for its effect on memory and cognitive impairment. Alzheimer’s disease (AD) is an area of intense scientific investigation due to its high prevalence and the lack of a definitive cure. Amyloid precursor protein plays a central role in Alzheimer’s disease by serving as the precursor for amyloid-β, the peptide responsible for the formation of toxic amyloid plaques. The dysregulation of APP processing in the amyloidogenic pathway leads to the accumulation of Aβ peptides and hyper-phosphorylation of tau disrupt neuronal function, induce oxidative stress, and activate neuroinflammatory responses. The synthetic drug samelisant that is in clinical trials with narcolepsy where they work as a H3 receptor reverse agonist serves as a potential candidate were studied. Recent studies have also shown their potential for treating excessive daytime sleep in Parkinson’s disease. The outcomes of the docking studies unveil their potential for treating Alzheimer’s disease. The samelisant was concluded to have good binding affinity with acetylcholine esterase, β secretase and tumor necrosis factor α cleaving enzyme, butyrylcholine esterase and binding affinity were found to be above –8 kcal/mol. This provides insights into their potential as an inhibitor or a modulator for AD.
Keywords: Alzheimer’s disease; molecular docking; molecular dynamics simulation; pi–pi stacking; samelisant